Scyld Scyldinga: Intercultural Innovation at the Interface of West and North Germanic. - Anderson, Carl (Neophilologus, 2016)
While many agree that Scyld in Beowulf was back-formed from Scyldingas, the context in which this occurred is rarely discussed. It seems frequently assumed that Scyld was created in Denmark and exported to England along with the name Scyldingas. However, the way that names and terms corresponding to Scyld and Scyldingas are used in medieval Scandinavian texts suggests that neither the figure nor an associated dynasty may have been very familiar to Scandinavians. Moreover, a consideration of Scandinavian place-name evidence shows that pre-medieval Scandinavian group-names in - ing-/- ung- were not formed on anthroponymic bases, though this practice was frequent in West Germanic contexts. Thus, though it is unlikely that Scandinavians in Scandinavia back-formed a figure named Scyld from a Scandinavian group-name antecedent to Scyldingas, such an interpretation would have been familiar and logical in West Germanic contexts. Accordingly, the figure of Scyld was likely back-formed by persons familiar with West Germanic naming practices and a Scandinavian form of Scyldingas, perhaps in an Anglo-Scandinavian context in Britain. Subsequently, the figure of Scyld was exported to Scandinavia and, though perhaps absent from autochthonous traditions, incorporated as accepted wisdom into written history and legend.